SYSTEMATIC RESEARCH OF DIGITAL MARKETING STRATEGY TOOLS (Economic journal of Lesya Ukrainka Volyn National University, 2021)
In the 21st century, when technology is evolving rapidly and there is unlimited access to information, there is no denying that the world we live in is changing rapidly. The rapid development of science, globalization, the transition to the information society and the digital economy have contributed to a significant transformation of society. Currently, the world is creating a global digital space, so globalization and digitalization - the main trends of today, which to a greater or lesser extent cover all countries. Digitalization is a general term for the digital transformation of society and the economy. It describes the transition from the industrial age and analog technologies to the age of knowledge and creativity, which is characterized by digital technologies and innovations in digital business. Of course, marketing has not been left out and has undergone significant changes in recent times, resulting in the concept of digital marketing. So еhe article establishes that digital marketing is a type of marketing activity that through digital channels by digital methods allows targeted interaction with target market segments in virtual and real environments. The marketing tools of the Internet are studied and the marketing communication strategy in the digital environment is considered as a component of the company's marketing complex, which determines the company's communication influence on market participants through the use of digital influence tools and active process moderation in the communication environment.
Keywords: digital marketing, Internet, communication, promotion, marketing tool, omnichannel marketing